NEEDANALYSIS DALAM MATA KULIAH ‘ENGLISH FOR SPECIFIC PURPOSES’ - Kusumaningputri, Reni (Jurnal Pengembangan Pendidikan, 2011)
Abstract. Need analysis for English for specificpurposes course is something very necessary. The benefits are for answering thequestions of needs which have been always specific for the learners themselves,and for the sake of make up purpose, that is to impress the students positivelythat the course is carried out seriously. The analysis is classified broadlyinto 3 categories; target situation analysis, learning analysis, and learneranalysis. The better the need analysis the more suitable the course will be.This paper aimed at describing how to do need analysis for a course namelyEnglish for Specific Purposes. Key words: need analysis, target situationanalysis, learning analysis, learners’ analysis